Humanity’s expensive banalities. Virtual Reality mediated Advertisement exploration for raising environmental awareness: augmented advertisement (2020)
The research engaged in this articles had as a goal analyzing the emotional perceptions of a focal group of young students from Fundación Universitaria los Libertadores with ages within a range from 17 to 23 years old, through an advertisement exercise that allowed the observation of the levels of remembrance generated by the exposition to the subjects of two advertisements in different time intervals: one of them with a traditional bidimensional format and the second one, the same piece translated into the emerging augmented reality technology. The methodology employed was an explorative one: it implied the development of three analysis and reading matrix-type tools. The first of them was composed for undergoing the translation process of the bi-dimensional piece to the enriched narrative with augmented reality, involving in its making which of the constitutive elements highlighted in importance over some that were not as important. The second one was employed for registering the emotional perceptions of the participants in the experiment, comparing the two kinds of pieces in two different moments; and with the third one, the aim was analyzing the attachment levels towards both pieces. These last two tools had as a goal registering the level of remembrance in time generated by the two spots presented. The research concludes that augmented reality generates impact among spectators and improves the remembrance capacity, but not in the levels expected. On the other hand, it is found that it was possible to incorporate positive design concepts for the translation and analysis of advertisements pieces that also work as a methodological medium for evaluating and registering the remembrance states. This facilitated the design and development process of an app for mobile devices as an extended augmented reality advertisement proposal —augmented advertisement—.